Is quantum mechanics pointless? - Arntzenius, F (2003)
There exist well-known conundrums, such as measure-theoretic paradoxes and problems of contact, which, within the context of classical physics, can be used to argue against the existence of points in space and space-time. I examine whether quantum mechanics provides additional reasons for supposing that there are no points in space and space-time.